PARENTS' PERCEPTIONS OF BOS FUNDING EDUCATION FINANCING IN SDN BASIRIH 1 BANJARMASIN - Riinawati (Lafadz Jaya Publisher, 2023)
The purpose of this study was to determine parents' perceptions of education funding for boss funds at SDN Basirih 1 Banjarmasin. This type of research is qualitative research with a phenomenological approach. The data sources in this study are parents, principals, school committees and supervisors who are taken through interview and documentation techniques. The research instruments used in this study include researchers and interview guidelines. The analysis technique used is the technique of analyzing and interpreting research data using the Miles and Huberman analysis model through three stages, namely; data reduction, data presentation, and conclusion drawing. The results showed that parents' perceptions of BOS funding education financing at SDN Basirih 1 Banjarmasin. Based on the results of the data obtained, parents' perceptions of BOS fund education financing at SDN Basirih 1 Banjarmasin, parents are very enthusiastic in responding to the policies issued by the government, namely the nine-year compulsory education program, both in terms of opinions, responses, and assessments of parents are very positive towards BOS fund education financing, this shows that the BOS fund education financing program is very helpful. Also, the implementation of BOS funding education financing at SDN Basirih 1 Banjarmasin, starting from the planning to the implementation stage, always includes all elements of the community to provide input to the school as well as oversee the implementation of the financing